Improving Student’s English Vocabulary Mastery through Scattergories Game - Dita Octaviana; Hastini Hastini; Sudarkam R Mertosono; Mochtar Mahrum (Hasanuddin University, 2025)
The intent of this study is to determine whether employing Scattergories Game is effective in order to enhance the vocabulary mastery of grade eighth students of SMP Negeri 2 Palu. The pre-experimental research design was utilized by the researcher. In determining the sample, the researcher employed a purposive sampling technique. The selected sample was class VIII B, comprising 32 students. Data were obtained through the use of both pre-tests and post-tests. The outcomes of the data analysis indicates that the mean score of student’s post-tests 85.06 is higher than students pretest score 57.97. The research findings that the t-counted value (31.157) is higher than the t-table value (2.039). This indicates that the hypothesis of the study is accepted. In conclusion, scattegories game is effective to improve students' vocabulary mastery of the student’s grade at SMP Negeri 2 Palu